Simultaneous detection of the subcellular localization of RNAs and proteins in cultured cells by combined multicolor RNA-FISH and IF - Meyer, Cindy (Methods, 2016)
Fluorescence in situ hybridization (FISH) and immunofluorescence (IF) are sensitive techniques for detecting nucleic acids and proteins in cultured cells. However, these techniques are rarely applied together, and standard protocols are not readily compatible for sequential application on the same specimen. Here, we provide a user-friendly step-by-step protocol to perform multicolor RNA-FISH in combination with IF to simultaneously detect the subcellular localization of distinct RNAs and proteins in cultured cells. We demonstrate the use of our protocol by analyzing changes in the subcellular distribution of RNAs and proteins in cells exposed to a variety of stress conditions.